The method for evaluation errors of automated measurements of base tangent length by three-axis indicator on five-axis CNC machine - D. T. Safarov; A. G. Kondrashov (Омский научный вестник)
The article provides an overview of studies of various errors in the process of measuring parts with three-coordinate probes on CNC machines. The paper considers a method for estimating systematic and random errors in the process of measuring the length of the base tangent using control maps and probabilistic and statistical methods for processing multiple repeated inputs of a three-coordinate indicator to the measured side surfaces of the wheel teeth. The method is designed to assess the acceptability of the measurement process by technologists and adjusters. The data of experimental estimation of random and systematic errors of measurement of the length of the base tangent on a five-coordinate CNC machine with a three-coordinate indicator of Mahr are presented. The obtained error values for the five-axis machine under study allow us to measure the length of the base tangent for the purposes of periodic monitoring and adjustment of the machine when processing oblique cylindrical wheels with universal disk or end mills.